Influence of zinc-solubilizing bacteria, zinc sulfate and organic acids on growth and yield of flooded rice - Othman, Nur Maizatul Idayu (2017)
Zinc (Zn) is an essential micronutrient required for plant growth. The unavailability of zinc due to the insoluble form cause deficiency of Zn in rice plant. Zincsolubilization bacteria (ZSB) has been known to aid in Zn solubilization in soil making zinc available for plants. A series of experiments were conducted in laboratory and glasshouse conditions with the following objectives; i) to isolate and characterize ZSB from rice roots and soil from Tanjung Karang Irrigation Area, Selangor, Malaysia ii) to evaluate the effects of different Zn rates on root colonization of rice plant inoculated with ZSB, iii) to determine the effects of ZSB inoculation, Zn sources and rates on growth of rice plant, iv) to determine the influence of ZSB inoculation, types and rates of organic acids and on Zn uptake and growth of rice plant applied with zinc sulfate and v) to determine the influence of ZSB, zinc sulfate and malic acid on growth and yield of rice. A total of 88 bacteria were isolated from rice soil and roots. Zincsolubilizing bacteria strains were evaluated for in vitro Zn solubilizing activity and characterized for multiple plant growth-promoting properties. Colonization and penetration of ZSB strains into rice roots were visualized using Scanning Electron Microscope (SEM) and Transmission Electron Microscope (TEM). Growth chamber study was conducted to determine the effects of ZSB, Zn sources and Zn rates on growth of rice using zinc oxide and zinc sulfate. The effect of ZSB on growth of rice in the presence of two organic acids (malic acid and citric acid) at four different rates (0, 0.1, 1.0 and 10 mM) was evaluated on growth of rice. Finally, glasshouse studies was conducted to determine the influence of ZSB strain Acinetobacter sp. (TM56), zinc sulfate and malic acid on Zn distribution in rice plant roots, rice grain yield and Zn fraction in zinc treated soils. Grain yield parameters were recorded after 120 days of growth. Zinc fraction in soil was referred to Community Bureau of Reference (BCR) sequential method. Results showed that nine of the isolates were able to solubilize the insoluble Zn. The highest Zn solubilizing efficiency (611%) was recorded by isolate TM67 in media supplemented with zinc carbonate. ZSB isolates were positive for nitrogen (N) fixation, phosphate solubilization, siderophore, indole- 3-acetic acid and hydrolyzing enzyme production. Two of the ZSB isolates (TM56 and TM23) were identified as Acinetobacter spp. and the other two (TM9 and BM13) were identified as Serratia sp. Micrographs of SEM and TEM showed the presence of ZSB strains in the intercellular spaces of rice root cells indicating their ability to colonise root surface and endosphere. Endosphere population of ZSB was differed with Zn rates in nutrient solution. Serratia sp. (TM9) showed highest endosphere population (5.56 CFU mL-1) at 0.2 mg L-1 of Zn rates compared to control. Application of ZSB, Zn sources and Zn rates increased plant growth. Plants inoculated with Acinetobacter sp. (TM56) with zinc sulfate at 0.2 mg L-1 showed the highest plant height (23.57 cm) compared to control. While, ZSB inoculation, organic acids and rates of organic acids increased plant growth and Zn uptake. In ZSB inoculated treatment with Acinetobacter sp. (TM56) and malic acid at 0.1 mM showed highest (777.64 mg 3 plant-1) Zn uptake, (39.57) SPAD reading , (29.57 cm) plant height and (135.67 mg) plant biomass were recorded compared to control. The EDX analysis showed that application of ZSB, zinc sulfate and malic acid in combination deposited highest Zn distribution (2.04 %) around exodermises and sclerenchyma of roots. The combined treatments showed highest filled spikelet (87.7 %) and harvest index (0.52). Zinc fractions in zinc treated soils was in the following order: residual > reducible > oxidisable > exchangeable. The combined treatments of ZSB, zinc sulfate and malic acid showed highest exchangeable (0.36 mg kg-1), oxidisable (0.26 mg kg-1) and reducible (0.35 mg kg-1) of Zn fraction compared to control. This study proved that application of ZSB, zinc sulfate and organic acids in combination was able to improve growth and Zn uptake of rice plant.